2012
DOI: 10.1128/aac.00771-12
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Respiratory Syncytial Virus Infectivity by a Dendrimeric Heparan Sulfate-Binding Peptide

Abstract: Respiratory syncytial virus (RSV) interacts with cell surface heparan sulfate proteoglycans (HSPGs) to initiate infection. The interaction of RSV with HSPGs thus presents an attractive target for the development of novel inhibitors of RSV infection. In the present study, a minilibrary of linear, dimeric, and dendrimeric peptides containing clusters of basic amino acids was screened with the aim of identifying peptides able to bind HSPGs and thus block RSV attachment and infectivity. Of the compounds identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 53 publications
1
50
0
1
Order By: Relevance
“…In view of this, the peptides derived from the natural COOH-terminal sequences of CXCL9 and CXCL12γ might be lead molecules for the generation of antiviral drugs that block the entry of viruses such as HSV-1, RSV and DENV-2 by binding to GAGs on target cells. The potency of these antiviral peptides may be increased by alternative formulations, as demonstrated for peptide-derived dendrimers [75][76][77][78]. As it is known that other viruses such as herpesviruses (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, the peptides derived from the natural COOH-terminal sequences of CXCL9 and CXCL12γ might be lead molecules for the generation of antiviral drugs that block the entry of viruses such as HSV-1, RSV and DENV-2 by binding to GAGs on target cells. The potency of these antiviral peptides may be increased by alternative formulations, as demonstrated for peptide-derived dendrimers [75][76][77][78]. As it is known that other viruses such as herpesviruses (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies are needed to determine whether mutagenesis of the additional 10 glycosylation sites abrogates the BA G enhanced cell-binding phenotype. Additionally, while heparan sulfate-containing GAGs are important for RSV infectivity in vitro (29,30,35), heparan sulfate-containing GAGs are not the most common GAGs found on the luminal surface of human airways or in mucus (36). Heparan sulfate GAGs may instead be one of multiple GAGs bound by RSV, and further work may identify the role of the duplicated region in BA G in binding to other GAGs, especially those found at higher frequency on airway cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of K5 derivatives that exhibit antiviral activity against a panel of HSPGs-dependent viruses, including HSV, HIV, and HPV (see the introduction), have been identified. Moreover, work from our own group has revealed the HSPGbinding dendrimer SB105A10 to be active against RSV infection (49), and the present study identifies additional K5 derivatives with capacities to block RSV infection. To provide further evi- dence corroborating the hypothesis that the anti-RSV abilities of these K5 derivatives depend specifically on their capacity to prevent RSV from interacting with HSPGs on the target cell, the compounds were tested against human rotavirus, whose attachment and entry depend on interaction with integrins and heat shock proteins but not HSPG (54).…”
Section: Resultsmentioning
confidence: 99%
“…Some antiviral compounds are known to lower cell susceptibility to viral infection by downregulating or directly masking virus receptors. In particular, we recently demonstrated that the compound SB-105A10 exerts its anti-RSV activity by masking HSPGs on the cell surface (49). To investigate whether the K5 derivatives affect cell susceptibility to RSV infection, preattachment assays were performed as described above.…”
Section: Resultsmentioning
confidence: 99%